ESTIMATION OF GENETIC PARAMETERS FOR GROWTH AND MORPHOMETRIC TRAITS IN SAHIWAL CATTLE BREED IN PAKISTAN - Sajida Naseem; Muhammad Sajjad Khan; Pervez Akhtar; Shaukat Ali Bhatti; Safdar Imran (Journal of Animal and Plant Sciences, 2024)
Genetic improvement in animals is based on selecting individuals for trait based on direct or indirect measurements. The present study was planned with the objectives of estimating genetic parameters for body weight and various morphometric traits to include them in the selection criteria for Sahiwal cattle. The animals (N=326) of both sexes (180 male and 146 females, from one month to adult age) having pedigree information were selected and body weight (BW), wither height (WH), hip height (HH), body length (BL), heart girth (HG) and paunch girth (PG) were measured thrice after an interval of 15-30 days. Genetic parameters were estimated using an animal model, with sex and five farms as fixed effects, and animal (error) as random effects. WOMBAT software was used for genetic analyses. Heritability estimates of BW, WH, HH, BL, HG and PG were 0.27±0.239, 0.18±0.171, 0.33±0.209, 0.26±0.209, 0.44±0.23 and 0.54±0.227, respectively. Genetic correlations of hip height with BW, WH, HH, BL, HG and PG were 0.63±0.772, 0.99±0.057, 0.59±0.313, 0.89±0.119 and 0.92±0.123, respectively. The Coefficient of determination to predict various body traits ranged between 88% and 97%. BW and HH could be predicted from age with high accuracy in both males (R2=95.0, 93.8%) and females (R2=96.3, 95.6%), respectively. WH and HH were strongly correlated; however, HH had slightly better genetic control and was easier to measure due to its independence from hump. It is concluded that hip height is a good indicator of animal height and can be used as selection criteria for Sahiwal cattle in Pakistan.
Keywords: Cattle; Genetic parameters; Biometry; Linear traits